The Lineup : The World's Greatest Crime Writers Tell the Inside Story of Their Greatest Detectives - Penzler, Otto. (New York : Back Bay Books, 2010)
Shares the stories behind the creations of many of the mystery genre's most popular characters, revealing the inspirations for such examples as Michael Connelly's Harry Bosch and Alexander McCall Smith's Precious Ramotswe.
Jack Taylor / by Ken Bruen -- Jack Reacher / by Lee Child -- Hieronymus Bosch / by Michael Connelly -- Charlie Parker / by John Connolly -- Elvis Cole and Joe Pike / by Robert Crais -- Lincoln Rhyme / by Jeffery Deaver -- Inspector Morse / by Colin Dexter -- Charlie Resnick / by John Harvey -- Bob Lee Swagger / by Stephen Hunter -- Peter Decker and Rina Lazarus / by Faye Kellerman -- Alex Delaware / by Jonathan Kellerman -- Dismas Hardy / by John Lescroart -- Tess Monaghan / by Laura Lippman -- Rambo / by David Morrell -- Mallory / by Carol O' Connell -- Spenser / by Robert B. Parker -- Lou Boldt / by Ridley Pearson -- Charlotte and Thomas Pitt / by Anne Perry -- Aloysius X. L. Pendergast / by Douglas Preston and Lincoln Child -- John Rebus / by Ian Rankin -- Precious Ramotswe / by Alexander McCall Smith.
Keywords: Detective and mystery stories, American -- Sources; Detective and mystery stories, English -- Sources; Characters and characteristics in literature; Detectives in literature; Detective and mystery stories -- Authorship; Novelists, American -- 20th century -- Biography; Novelists, English -- 20th century -- Biography